Economic development from the state & local perspective : case studies and public policy debates - Robinson, David J.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
This definitive work mixes case law, public policy, economic strategy, and examines the wide range of issues facing efforts to improve the American economy, to illustrate how economic growth is driven through strong public-private partnerships, and how successful growth strategies from the state and local level operate to grow jobs.
Keywords: Economic development -- United States; State governments -- United States; Local government -- United States; United States -- Economic policy -- 21st century